Systematic generation of manufacturing changes for safety-critical components. (July 2020) - Hermann, L.; Rey, J.; Barth, S.; Bergs, T.
Highlights: The increasing number of products changes poses a great challenge for the manufacturing of safety-critical components. Modelling interdependencies between a manufacturing process chain and component characteristics in a multiple domain matrix. A pairwise comparison considering information uncertainties enables technology planners to evaluate alternative adaptions.. An algorithm allows for the systematic analysis of the change propagation adaptions cause to an existing manufacturing. Abstract: Every time a component's design is changed, the corresponding manufacturing has to be changed as well. Due to several recent developments such as increasing market dynamics or ever-shorter product life cycles, the amount of component changes is rising sharply. Therefore, the number of manufacturing changes is increasing at a fast pace. Particularly for safety-critical components, the implementation of component changes within manufacturing poses a significant challenge. The reason for this is the high planning reliability required to implement a component change via a manufacturing change. This implementation has to be performed without endangering the component's functionality, by causing any other change than the intended one. An approach for the systematic generation of manufacturing changes was developed as a contribution to increasing planning reliability and efficiency. The approach systematically enables technology planners to identify alternative manufacturing changes, to analyze the propagation of these changes, and to evaluate the alternatives to form a basis for decision-making. Its practical applicability is validated using a case study from medical technology.